The Outsiders - Dillon, Matt; Macchio, Ralph George, 1961-; Howell, C. Thomas, 1966-; Swayze, Patrick; Lowe, Rob; Estevez, Emilio, 1962-; Cruise, Tom, 1962-; Lane, Diane; Garrett, Leif, 1961-; Rowell, Kathleen Knutsen; Roos, Fred; Frederickson, Gray; et al. (Burbank, CA : Warner Home Video, 2005)
Rivalry between rich and poor gangs in 1960s Oklahoma leads to a teenager's death and soul-searching for one of the youths involved. Includes twenty-two minutes of previously cut footage, a new soundtrack, commentary by director Francis Ford Coppola and six of the actors, readings by cast members of selections from the novel, screen tests and auditions, and other special features.
Based on the book by S.E. Hinton.
Originally produced as a motion picture in 1983.
Disc 1 includes feature and optional feature-length commentary by Francis Ford Coppola or cast members; disc 2 includes Staying gold : a look back at The Outsiders, S.E. Hinton on location in Tulsa, and The casting of The Outsiders featurettes; readings from the book by cast members; NBC News Today segment about the making of the film; additional scenes; and original theatrical trailer.
"Presented in a 'letterbox' widescreen format preserving the 'scope' aspect of its originial theatrical exhibition. Enhanced for widescreen TVs"--Container.
"Bonus materials not rated or closed-captioned"--Container.
Director of photography, Stephen H. Burum ; editor, Anne Goursaud ; music by Carmine Coppola.
Keywords: Family -- Fiction; Gangs -- Fiction; Video recordings for hard of hearing people; DVD-Video discs; Based on the book; Feature films